Efficient hydrosilylation of imines using catalysts based on iridium(iii) metallacycles. Issue 3 (26th November 2014) - Corre, Y.; Iali, W.; Hamdaoui, M.; Trivelli, X.; Djukic, J.-P.; Agbossou-Niedercorn, F.; Michon, C.
Abstract : Ir(iii ) metallacycles were applied as catalysts for the hydrosilylation of ketimines and aldimines by using sodium tetrakis[(3, 5-trifluoromethyl)phenyl]borate, NaBArF24, as an additive. By using a slight excess of the organosilane reagent, the reactions proceeded rapidly and efficiently, at low catalyst loadings and at room temperature. Abstract : Ir(iii ) metallacycles were applied as catalysts for the hydrosilylation of various ketimines and aldimines with sodium tetrakis[(3, 5-trifluoromethyl)phenyl]borate, NaBArF24, as an additive. By using a slight excess of the organosilane reagent, the reactions proceeded rapidly and efficiently, at low catalyst loadings and at room temperature. Several examples of cationic Ir(iii ) catalysts could be synthesised, characterized and tested. In situ -generated catalysts proved to be more active as compared to isolated ones and species with non-coordinating BArF24 counterion gave the highest catalytic activities.